Biochemical characteristics, genetic variants and treatment outcomes of 55 Chinese cases with neonatal intrahepatic cholestasis caused by citrin deficiency - Li, Juan; Duan, Jintao; He, Shuli; Li, Ying; Wang, Meifen; Deng, Chengjun (Frontiers in Pediatrics, 2025)
BackgroundThe diagnostic criteria of neonatal intrahepatic cholestasis caused by citrin deficiency (NICCD) have not been established due to non-specific clinical manifestations, and our understanding on the treatment outcome is still limited. We aim to investigate the biochemical characteristics, genetic variants, and treatment outcome of NICCD patients.MethodsWe compared the nutritional status and biochemical characteristics of 55 NICCD infants and 27 idiopathic neonatal cholestasis (INC) infants. SLC25A13 gene variant analysis was performed for definitive diagnosis of NICCD. NICCD infants received 12 months of lactose-free and/or medium-chain triglyceride-enriched (LF/MCT) formula treatment. The treatment efficacy was evaluated by comparing the outcome of NICCD with the 24 healthy infants that were selected as normal controls. All NICCD patients were followed up until death or at least 1 year of age.ResultsCompared to INC group, significant increase was found in levels of total bilirubin, indirect bilirubin, total bile acid, gamma-glutamyl transpeptidase, alkaline phosphatase, prothrombin time, thrombin time, international normalized ratio, alpha-fetoprotein (AFP), Vitamin D, and Vitamin E of NICCD group, while alanine aminotransferase, albumin, fibrinogen, glucose, and Vitamin A levels showed significant decrease in the NICCD group (P < 0.05). There were 7 novel variants among 19 SLC25A13 variant types. No significant differences were found between NICCD patients treated for 12 months and normal controls. In long term follow-up, 2 cases developed FTTDCD, 8 cases had special dietary habits, and 1 case died from cirrhosis.ConclusionsNICCD showed more severe impairments in liver, coagulation, and metabolic function than INC. Significantly increased AFP levels could provide reference for the differential diagnosis of NICCD. The newly discovered variants may be meaningful for the individualized treatment of NICCD patients. LF/MCT formula was recommended for NICCD patients.